Discharge characteristics of chemically prepared MnO2 and electrolytic MnO2 in non-aqueous electrolytes - Kim, HS; Kim, HJ; Cho, WI; Cho, BW; Ju, JB (ELSEVIER SCIENCE BV, 2002)
The discharge performance of chemically prepared MnO2 (CMD) and electrolytic MnO2 (EMD) is investigated in various electrolytes. LiPF6, LiCF3SO3, and LiBF4 are used as lithium salts in a mixed solvent of ethylene carbonate, propylene carbonate, and 1,2-dimethoxyethane (DME). The size and crystal structure of MnO2 particles is observed by scanning electron microscope and X-ray diffraction, respectively. The particle size of CMD is smaller than that of EMD, but the crystal structures of the two materials are similar. The concentration of dissolved manganese ions from CMD and EMD particles is 148 and 23 mg l(-1) in the same electrolyte, respectively. The interfacial electrochemistry of test cells is analyzed by impedance spectroscopy. The discharge performance is poor in the electrolyte containing LiCF3SO3 salt. The specific discharge capacity of CMD is superior to that of EMD at high discharge rate. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: LITHIUM